Host phenology can drive the evolution of intermediate virulence strategies in some obligate‐killer parasites. (7th May 2022) - MacDonald, Hannelore; Akçay, Erol; Brisson, Dustin
Abstract: Traditional mechanistic trade‐offs between transmission and virulence are the foundation of nearly all theory on parasite virulence evolution. For obligate‐host killer parasites, evolution toward intermediate virulence depends on a trade‐off between virulence (time to death) and transmission (the number of progeny released upon death). Although several ecological factors impact optimal virulence strategies constrained by trade‐offs, these factors have been insufficient to explain the intermediate virulence levels observed in nature. The timing of seasonal activity, or phenology, is a factor that commonly influences ecological interactions but is difficult to incorporate into virulence evolution studies. We present a mathematical model of a seasonal obligate‐killer parasite to study the impact of host phenology on virulence evolution. The model demonstrates that host phenology can select for intermediate parasite virulence even when a traditional mechanistic trade‐off between transmission and virulence is omitted. The optimal virulence strategy is impacted by both the host activity period duration and the host emergence timing variation. Parasites with lower virulence strategies are favored in environments with longer host activity periods and when hosts emerge synchronously. The results demonstrate that host phenology can be sufficient to select for intermediate virulence strategies, providing an alternative driver of virulence evolution in some natural systems.